MORFOLOGI DAN PERKEMBANGAN Palaenopsis anabilis Blume. (ORCHIDACEAE) - Tanta C Cornelis (NOVAE GUINEA Jurnal Biologi, 2015)
ABSTRACT            A study of morphology and development of Palaenopsis anabilis Blume. (Orchidaceae) was carried out to obtain the morphological development of flower, the characters of self incompatibility and some visitors insect. The methods to test a character of self incompatibility were outogamy and xenogamy pollination. The result of the research showed that an inflorescence raises from it’s stem, racemes, the anthesis centripetally (: racemosa) with hercogamy characters. The character of self incompatibility is 100 percent and potential insect in helping pollination is a garden bee (Bombus pensilvanicus). Key word :  Orchidaceae, Palaenopsis anabilis Blume., self incompatibility.